The Caregiving Experience of Wives of Veterans with Combat-Related Trauma and Dementia. - Czepiel, Teresa. (2017)
Abstract: Purpose. The purpose of this study was to describe the caregiving experiences of wives of combat-exposed veterans who now have dementia. There is growing investigation of intersections between combat-related trauma and dementia, but a paucity of research exists on adaptations that caregivers make between the two conditions. Methods. Semi-structured interviews were conducted with four wives of combat veterans with dementia. Data were transcribed and analyzed using qualitative description and content analysis. Findings. Themes clustered into two main categories: 1.) relationship; 2.) caregiver experience. Veterans' avoidance of conversation regarding combat experience, which had emotional impact on both the dyad and the wives, was common across participants. No clear demarcation between combat-related trauma and dementia was found. There were adaptations made to accommodate the avoidance of emotionally charged topics. Occupational therapists should be aware of the special needs and the caregiving experience of this particular cohort.; Thesis (M.S.)--Tufts University, 2012.; Submitted to the Dept. of Occupational Therapy.; Advisor: Scott Trudeau.; Committee: Linda Tickle-Degnen.; Keywords: Occupational therapy, and Gerontology.